2016
DOI: 10.14336/ad.2016.0402
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Magnesium Levels and Depression in Stroke Patients

Abstract: Post-stroke depression (PSD) is a common psychiatric complication of stroke that is associated with a poor outcome in stroke patients. Our aim was to assess the association between the serum magnesium levels and the presence of PSD in Chinese patients. Two hundred nine stroke patients were included in the study. Depressive symptoms were measured by the 17-Hamilton Rating Scale for Depression at 3 months after stroke. Based on the depressive symptoms, diagnoses of depression were made in line with the DSM-IV cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…Some authors found higher levels of serum Mg in depressed patient compared to healthy group [47,48] which are in contrast to our finding. On the other hand, several studies reported an inverse association between serum Mg levels and depression [49][50][51][52]. However, it seems serum Mg levels may not be a proper indicator of depressive disorders [52].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors found higher levels of serum Mg in depressed patient compared to healthy group [47,48] which are in contrast to our finding. On the other hand, several studies reported an inverse association between serum Mg levels and depression [49][50][51][52]. However, it seems serum Mg levels may not be a proper indicator of depressive disorders [52].…”
Section: Discussionmentioning
confidence: 99%
“…Mice subjected to magnesium deficient diets have shown behavioral deficits associated with depression [ 84 , 85 , 86 ]. Likewise, cross-sectional studies [ 26 , 87 , 88 , 89 ] have reported an inverse relationship between depressive symptoms and magnesium levels and magnesium intake, which persisted after adjustment for age, body mass index, and education. However, prospective cohort studies have failed to find an association between magnesium status and later risk of depression.…”
Section: Magnesiummentioning
confidence: 95%
“…Since Mg plays a crucial role in regulating the level of glutamate neurotransmitters in the brain, its deficiency predisposes PSD patients to experience increased severity of depressive symptoms [ 119 ]. Mg differs from other psychotherapy medications for PSD in that it is a dietary intervention.…”
Section: Current Drug Researchmentioning
confidence: 99%